Flavonoids enantiomer distribution in different parts of goldenrod (Solidago virgaurea L.), lucerne (Medicago sativa L.) and phacelia (Phacelia tanacetifolia Benth.). Issue 2 (4th January 2019) - Kruk, Judyta; Baranowska, Irena; Buszewski, Bogusław; Bajkacz, Sylwia; Kowalski, Bartosz; Ligor, Magdalena
Abstract: Plant material is a rich source of valuable compounds such as flavanones. Their different forms influence bioavailability and biological activity, causing problems with the selection of plant material for specific purposes. The purpose of this research was to determine selected flavanone (eriodictyol, naringenin, liquiritigenin, and hesperetin) enantiomer contents in free form and bonded to glycosides by an RP‐UHPLC‐ESI‐MS/MS method. Different parts (stems, leaves, and flowers) of goldenrod ( Solidago virgaurea L.), lucerne ( Medicago sativa L.), and phacelia ( Phacelia tanacetifolia Benth.) were used. The highest content of eriodictyol was found in goldenrod flowers (13.1 μg/g), where it occurred mainly as the ( S )‐enantiomer, and the greatest proportion of the total amount was bonded to glycosides. The richest source of naringenin was found to be lucerne leaves (4.7 μg/g), where it was mainly bonded to glycosides and with the ( S )‐enantiomer as the dominant form. Liquiritigenin was determined only in lucerne, where the flowers contained the highest amount (1.2 μg/g), with the ( R )‐enantiomer as dominant aglycone form and the ( S )‐enantiomer as the dominant glycosylated form. The highest hesperetin content was determined in phacelia leaves (0.38 μg/g), where it was present in the form of a glycoside and only as the ( S )‐enantiomer. A comparison of the different analyte forms occurring in different plant parts was performed for the first time. Abstract :